##### Find f(a), f(a + h), and the difference quotient f(a + h) − f(a) h , where h ≠

 Algebra Tutor: None Selected Time limit: 1 Day

f(x) = 5x2 + 4x − 10

f(
 2
)
=

f(x + 1) =

f(−x) =
f(x) = 2x + 8
f(a) =

f(a + h) =

 f(a + h) − f(a) h
=
f(x) = x2 + 6
f(a) =

f(a + h) =

 f(a + h) − f(a) h
=
f(x) = 3
f(a) =

f(a + h) =

 f(a + h) − f(a) h
=

Jun 28th, 2015

Thank you for the opportunity to help you with your question!

f(x) = 5x2 + 4x − 10

f(2)= 5(2)^2 + 4(2) − 10= 20+8-10= 18

f(x+1)=5(x+1)^2 + 4(x+1) − 10

= 5(x^2+1+2x)+ 4x+4-10

= 5x^2+5+10x+ 4x-6

= 5x^2+14x-1

f(-x) = 5x2 - 4x − 10

f(x) = 2x + 8

f(a) = 2a + 8

f(a+h) = 2(a+h) + 8= 2a+2h+8

[f(a+h)- f(a)]/h = [2a+2h+8 - 2a-8]/h

= [2h]/h= 2

f(x) = x2 + 6

f(a) = a^ 2+ 6

f(a+h) = (a+h)^2 + 6= a^2+h^2 +2ah +6

[f(a+h)- f(a)]/h = [a^2+h^2 +2ah +6 - a^2-6]/h

= [h^2+2ah]/h=  h+2a

f(x) = 3

f(a)=3

f(a+h)=3

[f(a+h)- f(a)]/h= (3-3)/h =0

please let me know if you have any problem in understanding the solution or need more clarification and details . i will be more happy to help you
please best me in review
best of luck :)

Please let me know if you need any clarification. I'm always happy to answer your questions.
Jun 28th, 2015

...
Jun 28th, 2015
...
Jun 28th, 2015
Dec 6th, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle